2021
DOI: 10.3389/fneur.2020.606418
|View full text |Cite
|
Sign up to set email alerts
|

Delayed-Release Dimethyl Fumarate Safety and Efficacy in Pediatric Patients With Relapsing-Remitting Multiple Sclerosis

Abstract: Background: Pediatric multiple sclerosis (MS) is rare: only 1.5–5% of MS cases are diagnosed before 18 years of age, and data on disease-modifying therapies (DMTs) for pediatric MS are limited. The CONNECTED study assessed the long-term safety and efficacy of treatment with delayed-release dimethyl fumarate (DMF), an oral MS DMT, in pediatric patients with MS.Methods: CONNECTED is the 96-week extension to FOCUS, a 24-week phase 2 study of patients aged 13–17 years; participants received DMF 240 mg twice daily.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…The safety and efficacy of dimethyl fumarate (Tecfidera ® ) in the POMS population was recently investigated in a small, single-arm, open-label study that consisted of an initial 8-week off-treatment period followed by a 24-week treatment period (FOCUS study; NCT02410200) [ 74 ]. An additional 96-week extension termed CONNECTED further followed the same patients that completed the FOCUS study [ 75 ]. All patients started the treatment with 1 week of dimethyl fumarate 120 mg twice a day (BID) and later escalated to the full adult dose of 240 mg BID.…”
Section: Use Of Disease-modifying Treatment In Pediatric Multiple Sclerosismentioning
confidence: 99%
See 3 more Smart Citations
“…The safety and efficacy of dimethyl fumarate (Tecfidera ® ) in the POMS population was recently investigated in a small, single-arm, open-label study that consisted of an initial 8-week off-treatment period followed by a 24-week treatment period (FOCUS study; NCT02410200) [ 74 ]. An additional 96-week extension termed CONNECTED further followed the same patients that completed the FOCUS study [ 75 ]. All patients started the treatment with 1 week of dimethyl fumarate 120 mg twice a day (BID) and later escalated to the full adult dose of 240 mg BID.…”
Section: Use Of Disease-modifying Treatment In Pediatric Multiple Sclerosismentioning
confidence: 99%
“…Over the entire 120-week follow-up through FOCUS and the CONNECTED extension, the ARR remained low at 0.2, an 84.5% reduction when compared with the year before entry into the study [ 75 ]. In the initial 24-week follow-up period, two patients had to discontinue the treatment due to an MS relapse and a case of urticaria, respectively [ 74 ].…”
Section: Use Of Disease-modifying Treatment In Pediatric Multiple Sclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…In the CONNECTED study (26), extension of FOCUS, a long-lasting benefit of therapy, was observed: 12/17 participants (71%) had no new/enlarged T2 hyperintense lesions from weeks 16 to 24. Over a mean treatment period of 120 weeks, a significant reduction of ARR compared with the year before DMF initiation was observed (from 1.5 to 0.2, p < 0.0001).…”
Section: Dimethyl Fumaratementioning
confidence: 98%